Posted by **Anonymous** on Saturday, February 2, 2013 at 7:29pm.

If f(x)= x^2-4 and g(x)= 2x-7

Find

a) f(g inverse(x))

b) g((g)inverse(x))

## Answer This Question

## Related Questions

- Math- steve? reiny? - 1. Let f(x)=x^5 + 2x^3 + x - 1 Find f^-1(3) and (f^-1)'(3...
- inverse - find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2...
- Advanced Algebra - What is the inverse of each of the functions defined by the ...
- Math - Find inverse of f if f(x)= x^2-4x+3, (for x is smaller than and equal to ...
- Pre-caluclus - I do not know how to solve for y to get the inverse of this ...
- math - The cost of producing q articles is given by the function C=f(q)=100+2q...
- Algebra - what is the inverse of the linear parent function? How would you graph...
- Pre-Calc - Does y=1/x have an inverse? It is a one-to-one function, so it should...
- Inverse of log function - Find the inverse of f(x) = log(2+x) - 4 the base is "a...
- algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...

More Related Questions